Effect of thermal calcinations on the charge transfer resistance of tantalum nitride nanotubes - Khan, Sherdil (2016)
Nanotubes of Ta3N5 were synthesized by thermal Nitridation of Ta2O5 nanotubes under ammonia gas environment. The effect of Nitridation temperature and time was evaluated. Electrochemical impedance spectroscopy was applied to study the charge transfer resistance across the Ta3N5 NTs/electrolyte interface. It was observed, at higher temperatures tubular morphology can be preserved for short nitridation time. The electrochemical impedance spectroscopy (EIS) revealed that nitridation conditions such as temperature and time strongly influence the interfacial charge transportation; affecting the photoelectrochemical (PEC) activities of the photoanodes.